Semantic dimensions of shape systems and their manifestations in graphic art (Al-Academy, 2024)
Graphic art is one of the most important means of human expression and communication as it is a universal expressive language that addresses all human beings. Therefore، it was necessary to study the formal systems of global graphic art because of its ability to reduce the semantic dimensions and treatments in graphic design، which is essentially a means of expressing ideas aesthetically and functionally. Chapter One: Reviewing the research problem that was identified by answering the following question: What are the semantic dimensions of shape systems and do they have manifestations in graphic art? The research aimed to: identify the semantic dimensions of shape systems and their manifestations in graphic art، and the chapter concluded with a definition of terms. As for the second chapter. It included three topics: the first: graphic art، a historical overview of its origins and development، the second: shape systems in graphic design، and the third: graphic art techniques. The chapter concluded with indicators of the theoretical framework and a discussion of previous studies. Chapter Three: The researchers adopted the descriptive analytical method، and the research community included (20) samples. (4) samples were selected and an analysis tool was prepared and criteria for validity and reliability were extracted. In Chapter Four: the most important results reached were reviewed، and among them were: I took Advertising in graphic drawing is a state of turning towards dramatic contents، such as an invitation to musical clamor and written employment. The lithographic printing technique in model (2) shows digital semantic dimensions of form systems. The chapter concluded with a number of recommendations and suggestions